2021
DOI: 10.1002/ceat.202100256
|View full text |Cite
|
Sign up to set email alerts
|

Shortcut Method for Initialization of Dividing‐Wall Columns and Estimating Pareto‐Optimal NQ‐Curves

Abstract: In early project stages, often no simulation results are available for dividing‐wall columns. Hence, shortcut methods are used to estimate suitable vapor and liquid splits. In a previous paper, it was demonstrated that V · min diagrams are a suited tool to satisfy this need. However, it has turned out that it shows weaknesses for columns with finite or non‐optimal stages. This contribution closes that gap and presents an extended approach to derive suited initial guesses. For this purpose, the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…[12][13][14]16 Even though the V ̇min diagram was originally intended for the minimum energy demand case, it was shown that it can also be extended to finite number of stages. 17 The so-called stageadapted V ̇min diagram helps us understand the actually performed separation task at a given number of stages and energy input.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[12][13][14]16 Even though the V ̇min diagram was originally intended for the minimum energy demand case, it was shown that it can also be extended to finite number of stages. 17 The so-called stageadapted V ̇min diagram helps us understand the actually performed separation task at a given number of stages and energy input.…”
Section: Theoretical Backgroundmentioning
confidence: 99%